Book Review: Visions of Utopia: Nashoba, Rugby, Ruskin, and the “New Communities” in Tennessee's Past. By John Egerton. (Knoxville: University of Tennessee Press, Tennessee Historical Commission, 1977. 95 pp. Maps, illustrations, more resources, and index. Paper, $3.50.) - Caruthers, J. Wade (Journal of American History, 1978)
J. Wade Caruthers; Visions of Utopia: Nashoba, Rugby, Ruskin, and the “New Communities” in Tennessee's Past. By John Egerton. (Knoxville: University of Tenness
Keywords: book.review; dept.his